2010
DOI: 10.5194/bgd-7-7607-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep plant-derived carbon storage in Amazonian podzols

Abstract: Equatorial podzols are soils characterized by thick sandy horizons overlying more clayey horizons. Organic matter produced in the topsoil is transferred in depth through the sandy horizons and accumulate at the transition, at a depth varying from 1 to more than 3 m, forming deep horizons rich in organic matter (Bh horizons). Although they cover great surfaces in the equatorial zone, these soils are still poorly known. Studying podzols from Amazonia, we found out that the deep Bh horizons in poorly drain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
0
12
0
9
Order By: Relevance
“…(); see Supporting Information for further details). Field efforts have confirmed peat presence in region 1, in the middle Rio Negro Basin (Lähteenoja et al., ) and in the upper Rio Negro Basin (Bardy, Derenne, Allard, Benedetti, & Fritsch ; Do Nascimiento et al., ; Dubroeucq & Volkoff, ; Horbe, Horbe, & Suguio, ; Montes et al., ). Extended peat deposits have been described in region 5, in the north‐western Amazonian Pastaza–Marañón river basins (Lähteenoja et al., ; Draper et al., ; up to 9 m).…”
Section: Discussionmentioning
confidence: 89%
“…(); see Supporting Information for further details). Field efforts have confirmed peat presence in region 1, in the middle Rio Negro Basin (Lähteenoja et al., ) and in the upper Rio Negro Basin (Bardy, Derenne, Allard, Benedetti, & Fritsch ; Do Nascimiento et al., ; Dubroeucq & Volkoff, ; Horbe, Horbe, & Suguio, ; Montes et al., ). Extended peat deposits have been described in region 5, in the north‐western Amazonian Pastaza–Marañón river basins (Lähteenoja et al., ; Draper et al., ; up to 9 m).…”
Section: Discussionmentioning
confidence: 89%
“…Thick, white, clayey kaolinitic saprolite, which can be regarded as kaolin, has also been observed beneath ferralsol‐podzol soil systems developed over sedimentary rocks in the Manaus area (Chauvel et al , ; Costa & Moraes, ) or over crystalline basement rocks in French Guyana (Veillon, ) and in the High Rio Negro area (Dubroeucq & Volkoff, ; Montes et al , ). These soil systems, whose dynamics are characterized by a progressive replacement of ferralsol by podzol, are widespread throughout a large part of the Amazon area: more than 18% is covered by ferralsol‐podzol systems and podzols cover most of the Upper Rio Negro region (Dubroeucq & Volkoff, ; Montes et al , ). All these studies concluded that the white kaolinitic saprolite was formed by bleaching and kaolinization of the parent material with a partial dissolution of quartz grains.…”
Section: Introductionmentioning
confidence: 99%
“…In order to test this, a ferralsol-podzol system that features a thick, bleached kaolin horizon at depth was chosen for a detailed mineralogical and geochemical study. The chemistry of the percolating solutions and the quantification of the podzolic SOM were described in Montes et al, 2011 andLucas et al, 2012. The aim of the present paper is to detail the relationships between the mineralogical features and the geochemistry of the soil cover and to infer the conditions of the kaolin genesis and the long-term dynamics of the soil cover.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations